A discrete choice experiment to determine UK patient preference for attributes of disease modifying treatments in Multiple Sclerosis. (3rd August 2017) - Bottomley, Catherine; Lloyd, Andrew; Bennett, Gary; Adlard, Nicholas
Abstract: Aims: The recent licensing of Disease Modifying Treatments (DMTs) for Multiple Sclerosis (MS) has increased available treatment options. The aim of this study was to explore MS patients' preference for the different attributes of DMTs in the UK. Materials and methods: Attributes (treatment characteristics) for inclusion in the discrete choice experiment (DCE) were determined through published literature and interviews with 12 people with MS. Seven attributes were selected. Participants were presented with three hypothetical treatment options sampled from included attributes and asked for their most/least preferred options. The influence of patient characteristics and demographics on patient preference was also investigated. Results: The DCE was completed by 350 people with MS (81% female, mean age = 39). Results showed that method of taking medication was the strongest determinant of preference (27%; relative importance out of 100%), followed by relapse free rate (21%) and symptom progression (14%). Risk of fatigue (8%) and type of monitoring (6%) were the weakest determinants of preference. Once-daily oral treatment was preferred over all other methods of administration. Participant characteristics did not influence data on strength of preference. Limitations: This study assumed adequate participant understanding of the discrete choice experiment task, and recruitment targeted those with access to the internet. Conclusions: These results, derived from people with MS in the UK, should be used to inform individual discussions with patients about DMT choices.